Single-cell view and a novel protective macrophage subset in perivascular adipose tissue in T2DM - Jiaxuan Li; Zhenyu Tian; Tongxue Zhang; Jiajia Jin; Xinjie Zhang; Panpan Xie; Haiyan Lin; Junfei Gu; Yingjie Wu; Xiaowei Wang; Shucui Zhang; Xuefang Yan; et al. (Cellular & Molecular Biology Letters)
Abstract Background Vasculopathy underlies diabetic complications, with perivascular adipose tissue (PVAT) playing crucial roles in its development. However, the changes in the cellular composition and function of PVAT, including the specific cell subsets and mechanisms implicated in type 2 diabetes mellitus (T2DM) vasculopathy, remain unclear. Methods To address the above issues, we performed single-cell RNA sequencing on the stromal vascular fraction (SVF) of PVAT from normal and T2DM rats. Then, various bioinformatics tools and functional experiments were used to investigate the characteristic changes in the cellular profile of diabetic PVAT SVF, their implications, and the underlying mechanisms. Results Our study reveals the single-cell landscape of the SVF of PVAT, demonstrating its considerable heterogeneity and significant alterations in T2DM, including an enhanced inflammatory response and elevated proportions of macrophages and natural killer (NK) cells. Moreover, macrophages are critical hubs for cross-talk among various cell populations. Notably, we identified a decreased Pdpn + macrophage subpopulation in the PVAT of T2DM rats and confirmed this in mice and humans. In vitro and in vivo studies demonstrated that Pdpn + macrophages alleviated insulin resistance and modulated adipokine/cytokine expression in adipocytes via the Pla2g2d-DHA/EPA-GPR120 pathway. This subset also enhances the function of vascular endothelial and smooth muscle cells, inhibits vascular inflammation and oxidative stress, and improves vasodilatory function, thereby protecting blood vessels. Conclusion Pdpn + macrophages exhibit significant vascular protective effects by alleviating insulin resistance and modulating adipokine/cytokine expression in PVAT adipocytes. This macrophage subtype may therefore play pivotal roles in mitigating vascular complications in T2DM. Our findings also underscore the critical role of immune-metabolic cross-talk in maintaining tissue homeostasis. Graphical Abstract